Overview of formulation & evaluation of fast dissolving tablet: A promising tablet dosage form - Akash Babu; Akhtar, Md. Semimul (Creative Pharma Assent, 2020)
The science of drug delivery has been increasingly innovative and quick evolving with ever-increasing demand in the current scientific scenario. Fast dissolving tablet (FDT) is one of those forms of an advanced and special drug delivery system that is rapidly gaining a lot of attention in the rapid dissolution technology research sector. Fast dissolving tablets appear as one of the common and widely accepted dosage types, particularly for paediatric patients due to incomplete muscle and nervous system development and a form of geriatric patients with Parkinson's disease or hand shivering. The most popular administrative path for different medications has drawbacks such as first-pass metabolism, psychotic patients, bedridden and Uncollaborative patients, is the oral delivery type and oral path FDTs disintegrate or quickly dissolve in the saliva without requiring water. Within few seconds, FDT will dissolve within saliva for approximately 60 seconds and these comprises will dissolve even faster